2002
DOI: 10.1303/aez.2002.487
|View full text |Cite
|
Sign up to set email alerts
|

Records of two citrus pest whiteflies in Japan with special reference to their mating sounds (Homoptera: Aleyrodidae).

Abstract: A serious citrus pest, the ash whitefly, Siphoninus phillyreae Haliday, was first recorded in Honshu and Kyushu, Japan. The favored host plant is pomegranate (Punica granatum L.) from early summer to autumn. The adults migrate to a hedge plant (Photinia glabra (Thumb.) Maxim.) or rarely to a citrus plant (Citrus natsudaidai Hayata) before pomegranates shed their leaves in winter. Another citrus pest, the woolly whitefly, Aleurothrixus floccosus Maskell, was found from Nansei Islands to north of Tokunoshima Is.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Cuticular hydrocarbons (CHCs) secreted from a variety of glands and accumulated on the external surface of the exoskeleton have been shown to act as contact signals for species, kin and mate recognition in numerous species of insects (Howard, 1993; Howard & Blomquist, 2005; Dani, 2006; South et al , 2008; De Barro et al , 2011). Whitefly males and females have also been shown to exchange reciprocal sounds during mate finding and courtship leading to copulation (Kanmiya, 1996; Kanmiya & Sonobe, 2002). It seems likely that CHCs, acoustic signals, or possibly both may play a role in mate recognition in B. tabaci .…”
Section: Discussionmentioning
confidence: 99%
“…Cuticular hydrocarbons (CHCs) secreted from a variety of glands and accumulated on the external surface of the exoskeleton have been shown to act as contact signals for species, kin and mate recognition in numerous species of insects (Howard, 1993; Howard & Blomquist, 2005; Dani, 2006; South et al , 2008; De Barro et al , 2011). Whitefly males and females have also been shown to exchange reciprocal sounds during mate finding and courtship leading to copulation (Kanmiya, 1996; Kanmiya & Sonobe, 2002). It seems likely that CHCs, acoustic signals, or possibly both may play a role in mate recognition in B. tabaci .…”
Section: Discussionmentioning
confidence: 99%
“…Cuticular hydrocarbons (CHCs) secreted from a variety of glands and accumulated on the external surface of the exoskeleton have been shown to act as contact signals for species, kin and mate recognition in numerous species of insects (Howard, 1993; Howard & Blomquist, 2005; Dani, 2006; South et al , 2008). Whitefly males and females have also been shown to exchange reciprocal sounds during mate‐finding and courtship leading to copulation (Kanmiya, 1996; Kanmiya & Sonobe, 2002). Recent work on Laupala crickets demonstrated both interspecific and sex differences in CHC composition, and suggested that acoustic signals were used for long‐range mate attraction while CHCs functioned in close‐range species discrimination (Mullen et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Flavescence dorée Papura et al, 2012Mazzoni et al, 2009Polajnar et al, 2014Polajnar et al, 2016 Smaller green leafhopper, Empoasca vitis Göthe Nieri and Mazzoni, 2018Taylor, 1985Tishechkin, 2006Diaphorina citri Kuwayama Huanlongbing, HLB 19982008HLB Bové, 2006Alvarez et al, 2016Bayles et al, 2017 , 1981Li and Maschwitz, 1985Li et al, 1989B Zang and Liu, 2007Kanmiya 1996 1998 Kanmiya and Sonobe, 2002Kanmiya, 2006Kanmiya et al, 2011 150 450 Hz 5 1 3 LED Kanmiya 1996 35 mm Kanmiya, 1996Kanmiya and Sonobe, 2002Kanmiya, 2006Kanmiya et al, 2011Nakabayashi et al, 2015 Step 1…”
Section: Hzmentioning
confidence: 99%